Pratiche di consumo alla prova del Covid-19 - Bartoletti, Roberta; PALTRINIERI, ROBERTA; PARMIGGIANI, PAOLA (Consumo, Comunicazione, Innovazione, 2022)
How do the consumption practices and meanings of a community change in the face of an event as exceptional as a global pandemic? The phase of emergency has altered not only the balance between the material and the digital dimension in our consumption, but also our relationship with the domesticity and the neighboring relations. Some of these changes could form the basis of long-lasting innovations; others, however, have already failed or are destined to disappear. The volume brings together reflections and analyses, based on both qualitative as well as quantitative methodologies, regarding how the health, cultural, and social emergency of Covid-19 was addressed through the consumption and its ordinary, everyday practices - shopping, cooking and eating, the practices of fashion, cultural consumption and leisure - as well as how advertising narratives changed during the different phases of the pandemic to synchronize with the experiences of Italian consumers.